Community gardening, community farming and other local community-based gardening interventions to prevent overweight and obesity in high-income and middle-income countries: protocol for a systematic review. Issue 6 (15th June 2017) - Heise, Thomas L; Romppel, Matthias; Molnar, Sandra; Buchberger, Barbara; Berg, Agnes van den; Gartlehner, Gerald; Lhachimi, Stefan K
Abstract : Introduction: The worldwide prevalence of overweight/obesity has continued to rise over the last decades. To reverse this trend, public health authorities are exploring cost-effective interventions, especially in high-income and middle-income countries. Community gardening offers a unique opportunity for individuals to enhance physical activity levels and improve their diet. However, synthesised evidence on the short-term or long-term effectiveness and on the costs of community gardening interventions to prevent overweight/obesity remains limited. Therefore, this review will investigate: (1) the effectiveness of voluntary participation in community gardening compared with no or a control intervention on overweight/obesity and associated health outcomes, (2) effects on different subgroups of populations and (3) the costs of community gardening interventions. Methods and analysis: We will conduct a systematic review, limited to evaluations of community gardening interventions with controlled quantitative and interrupted time series designs. To identify relevant articles, we will systematically search 12 academic and 5 grey literature databases, as well as 2 trial registers and 6 websites. Articles will then be assessed for eligibility based on a predefined set of criteria. At least two independent reviewers will assess each article for relevance, before evaluating the methodological quality and potential bias of the studies. Data relevant to the objectives of this review will be extracted and cross-validated. Any disagreements will be mediated by a third reviewer. If feasible, meta-analyses of primary outcomes (overweight/obesity, physical activity, food intake, energy intake) will be conducted. We will use the Grading of Recommendations Assessment, Development and Evaluation method to assess the overall quality of evidence. Ethics and dissemination: For this review, no ethical approval is required as we will only extract and analyse secondary data. We aim to submit the final review manuscript to an open access journal for publication and disseminate results via conferences and social media. Trial registration number: International Prospective Register of Systematic Reviews (PROSPERO)(CRD42017043696).